Counseling on Productive Economic Business Empowerment for the Communities of Muara Kumbang Village, Kandis Sub-District, Ogan Ilir District - Pratama, Akram; Fitria, Dinda; Ilham, M.; Puput, Puput; Zubaidah, Zubaidah; Delimawati, Delimawati; Fatri, Tri; D., Sukaria (Universitas Muhammadiyah Palembang, 2021)
Empowerment is an effort to create changes in the human environment by using one's own efforts and abilities to meet the needs of life independently. Based on the situation analysis conducted in Muara Kumbang village, Kandis sub-district, Ogan Ilir district, it is very necessary to do community service with the theme of